The patients‘ perspective - a qualitative analysis of experiencing a fracture-related infection - Wimalan, Bravena; Rupp, Markus; Alt, Volker; Walter, Nike (Frontiers in Psychology, 2023)
Introduction Fracture-related infection is a devastating complication confronting the patient with several challenges. To improve the management and to enhance the patients’ wellbeing the focus of this study was to understand the emotional impact and patients’ experiences during the process to identify challenges, difficulties, and resources. For this, a qualitative content analysis of semi-structured interviews according to Graneheim and Lundman was performed. Methods In total n = 20 patients of a German university orthopedic trauma centre specialized in bone and joint infections were recruited using a purposive sampling strategy. The patients were treated at the hospital between 2019 and 2021 and underwent at least one surgery. Individual in-person interviews were performed by one researcher based on a semi-structured guide, which was previously conceptualized. Content analysis according to Graneheim and Lundman was performed on the transcripts by two of the researchers independently. Results The following major themes emerged: (i) the emotional and mental aspects highlighting the fact that FRI patients faced severe restrictions in their day-to-day life, which resulted in dependency on others and frustration, as well as future concerns showing that patients could not overcome a state of anxiety and fear even after successful treatment, (ii) socioeconomic consequences confronting patients with consequences on the job and in finances where they often feel helpless, and (iii) resources emphasizing the role of spirituality as a coping strategy and yoga exercises for keeping the positivity. Conclusion This study emphasized the challenge of fracture-related infection management and associated consequences from the patients’ perspective. Not being well informed about possible negative outcomes or restrictions makes it harder for patients to accept the situation and patients expressed a need for better information and certainty. Also, patients developed constant anxiety and other psychological disturbances, highlighting the potential benefit of psychological support and patient-peer support to exchange experiences.